Intranasal Insulin Administration Dose-Dependently Modulates Verbal Memory and Plasma Amyloid-β in Memory-Impaired Older Adults - Reger, Mark A.; Watson, G. Stennis; Green, Pattie S.; Baker, Laura D.; Cholerton, Brenna; Fishel, Mark A.; Plymate, Stephen R.; Cherrier, Monique M.; Schellenberg, Gerard D.; Frey II, William H.; Craft, Suzanne (Journal of Alzheimer's disease, 2008)
Intranasal insulin administration raises central nervous system (CNS) insulin levels in humans and acutely facilitates verbal memory in patients with Alzheimer's disease (AD), an effect that may differ by APOE genotype. The purpose of this study was to examine the cognitive dose response curves for intranasal insulin administration, and determine whether the effects of insulin differ between participants with (ε4+) and without (ε4−) the APOE- ε4 allele. On separate mornings, 33 memory-impaired adults with AD or amnestic mild cognitive impairment and 59 normal adults each underwent five intranasal treatment conditions consisting of insulin (10, 20, 40, or 60 IU) or placebo. Cognition was tested 15-minutes post-treatment, and blood was acquired at baseline and 45-minutes post-treatment. Plasma insulin and glucose levels were unaffected by treatment. Insulin administration facilitated recall on two measures of verbal memory in memory-impaired ε4− adults, with performance generally peaking at 20 IU. In contrast, memory-impaired ε4+ subjects demonstrated a relative decline in verbal memory. Insulin also differentially modulated plasma amyloid-β for memory-impaired subjects and normal controls, effects that again differed by APOE genotype. These findings suggest that groups with different genetic risks for AD may show differential dose-response curves following intranasal insulin administration.